On analysis of the elektromagnetic resistance of radioelektronic devices under impulse radiation - Lonin, Yu. F.; Ponomaryov, A. G.; Chumakov, V. I. (NSC KhIPT, 2018)
The results of investigations on degradation effects in the radioelectronics circuit ryunder the influence of the high-intensity pulse radiation are given. Analysis of the mechanism of degradation because of hortening the radio pulse radiation wave length has been carried out. When the wavelength of the object, exposed to the radiation of a centimeter range, exceeds the characteristic size of structural elements, the degradation mechanism is conditioned by the quasi-static effects on the object structureinhomogeneities. The degradation effects manifest themselves in a c-cordance with the concept of a "weak link" and localization damage model. In the case of wavelength shortening, when the characteristic size of the objectstructure elementbecomes commensurable with the wavelength, the resonance effectaction is more and more increasing. The degradation redistribution occurs according to the field intensity distribution in the resonantregions. The problem of electromagnetic resistance lowering, under conditions of the tendency towards the radio electronics circuitry microminiaturization, is discussed.
Keywords: Electromagnetic resistance; Radioelectronic Device; Impulse Radiation